Diagnosing cardiovascular disease in western lowland gorillas (Gorilla gorilla gorilla) with brain natriuretic peptide. - Suzan Murray; Jennifer C Kishbaugh; Lee-Ann C Hayek; Ilana Kutinsky; Patricia M Dennis; William Devlin; Katharine L Hope; Marietta D Danforth; Hayley W Murphy (PLoS ONE, 2019)
Cardiovascular disease is a leading cause of death in zoo-housed great apes, accounting for 41% of adult gorilla death in North American zoological institutions. Obtaining a timely and accurate diagnosis of cardiovascular disease in gorillas is challenging, relying on echocardiography which generally requires anesthetic medications that may confound findings and can cause severe side effects in cardiovascularly compromised animals. The measurement of brain natriuretic peptide (BNP) has emerged as a modality of interest in the diagnosis, prognosis and treatment of human patients with heart failure. This study evaluated records for 116 zoo-housed gorillas to determine relationships of BNP with cardiovascular disease. Elevations of BNP levels correlated with the presence of visible echocardiographic abnormalities, as well as reported clinical signs in affected gorillas. Levels of BNP greater 150 pb/mL should alert the clinician to the presence of myocardial strain and volume overload, warranting medical evaluation and intervention.